2014
DOI: 10.1002/ps.3861
|View full text |Cite
|
Sign up to set email alerts
|

Detection of knockdown resistance mutations in the common bed bug, Cimex lectularius (Hemiptera: Cimicidae), in Australia

Abstract: The novel mutation I936F may be a kdr mutation but appeared to contribute less resistance to the pyrethroids than the V419L and L925I mutations. The detection of high frequencies of kdr mutations indicates that kdr-type resistance is widespread across Australia. Hence, there should be a reduced reliance on pyrethroid insecticides and an integrated management approach for the control of C. lectularius infestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 37 publications
2
77
0
Order By: Relevance
“…Several studies showed that kdr -type resistance to DDT and pyrethroids results from a single or multiple point mutations (also known as kdr mutations) in coding sequences of VGSC in various insect pests (Fig. 2) [46, 150, 154, 155], including bed bugs [17, 54, 156, 157]. Yoon et al [156] first cloned and sequenced the coding gene of C. lectularius VGSC from both insecticide resistant and susceptible strains in the USA.…”
Section: Mechanisms Of Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…Several studies showed that kdr -type resistance to DDT and pyrethroids results from a single or multiple point mutations (also known as kdr mutations) in coding sequences of VGSC in various insect pests (Fig. 2) [46, 150, 154, 155], including bed bugs [17, 54, 156, 157]. Yoon et al [156] first cloned and sequenced the coding gene of C. lectularius VGSC from both insecticide resistant and susceptible strains in the USA.…”
Section: Mechanisms Of Resistancementioning
confidence: 99%
“…One hundred percent of the tested C. lectularius collected from Paris, France [158] and Berlin, Germany [159] only contained L925I. Of C. lectularius collected from various locations in Australia (25 strains), 96% possessed L925I [55], while from Israel (12 strains), 100% had L925I, of which, a few specimens from both countries had additional V419L [54, 160]. Based on the various genotypes of V419L and L925I mutations of 110 field-collected strains of C. lectularius in the USA, Zhu et al [157] identified four haplotypes; haplotype A (without V419L and L925I mutations; 15.5% [17/110]), haplotype B (only L925I; 40.9% [45/110]), haplotype C (V419L and L925I; 40.9% [45/110]) and haplotype D (V419L; 2.7% [3/110]).
Fig.
…”
Section: Mechanisms Of Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…This strain has been extensively profiled for potential mechanisms conferring pyrethroid resistance, and has been found to possess haplotype B (homogeneous L925I) kdr -type resistance [13], hydrolytic esterase-derived metabolic detoxification [52], and cuticle thickening [50]. Exposure to a d-allethrin based rapid resistance field assay elicits no statistically significant levels of knockdown when compared to an untreated control [53].…”
Section: Methodsmentioning
confidence: 99%
“…Key amongst these has been a response to the growing global evidence that most field bed bug populations have developed resistance to multiple insecticide groups [5,6,7,8,9,10] and, in particular, that they have become highly resistant to pyrethroid insecticides [11,12,13,14,15,16,17,18,19,20,21,22,23]. Despite this, and due to a general scarcity of alternative control options [24], when faced with a bed bug infestation both pest management professionals (PMPs) and residents of infested properties continue to apply insecticides in attempts to achieve control [24,25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%